Pembuatan Trigliserida Kaya Asam Lemak ï·-3 dari Minyak Hasil Samping Pengalengan Ikan Lemuru (Sardinella longiceps) - Estiasih, Teti; Ahmadi, Kgs. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2004)
Omega-3 fatty had benefial effect for health.Â Fish oil from by product of lemuru canning process was a potential source of w-3 fatty acids.Â This fish oil had to be refined by alkali to fulfill the standar of crude fish oil.Â The w-3 fatty acids content in this fish oil (in the triglyceride form) could be enhanced by rapid solidification.Â Modification to this process was done therefore the process was easier to handle and cheaper.Â Modified rapid solidification could enrich the w-3 fatty acids content in the triglyceride form 1,87.Â The residue of this process could be used as raw materialÂ of the rapid solidification. Â Key words: w-3 fatty acids, triglyceride, alkali refining, rapid solidification.